Indonesia Agricultural Transformation: How Far? Where Would It Go? - Muhammad Abduh (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
This research examined the inequality that emerges as Indonesia's economy shifts from an agricultural to a non-agricultural sector at the subnational level. These research questions include: (1) How has the agricultural sector in the Indonesian provinces changed over the past two decades? (2) What was the widespread impact of several socioeconomic variables on the transformation of agriculture? (3) How has the agricultural sub-sector responded to the dynamics of these socioeconomic factors over the last decade? The scope of the analysis was the whole province of Indonesia, with time series between 2001-2018. The shift in agriculture at the provincial level was mapped using indicators of poverty and the sector's economic contribution to each province. The logistic regression method was used to see the impact of socioeconomic factors on the agricultural transformation. In contrast, the panel regression was applied to respond to the dynamics of the agricultural sub-sector in terms of socioeconomics in the last ten years. According to the findings of agricultural transformation mapping, there were no changes in the distribution of rural poverty or the agricultural contribution factors between the provinces. Several macroeconomic, social, and infrastructure development factors also significantly contributed to encouraging agricultural transformation and enhancing the added value of the agricultural sector as a whole. It was important to better efficiently utilize the economic potential, which was done by taking production efficiency into account. Furthermore, consumer behaviour and the level of worker productivity had to be considered in attempts to boost economic productivity.